Population Displacement and Housing Dilemmas Due to Catastrophic Disasters - Levine, Joyce N.; Esnard, Ann-Margaret; Sapat, Alka (Journal of Planning Literature, 2007)
As Hurricane Katrina revealed, coastal communities have become far more vulnerable to tropical storms and the long-term displacement of residents. Yet, because the emergency management model presumes that recovery quickly follows response, governments focus only on short-term, localized displacement. However, long-term and long-distance displacement exposes a gray area between immediate shelter and permanent housing, along with concerns about vulnerability, housing availability, and land development. We begin this article by discussing the transition between response and recovery. We then review literature regarding social vulnerability, displacement, provision of temporary housing, households' return decisions, and disaster-driven land development and housing construction processes. We close with thoughts on future research to increase planners' understanding of the issues involved and to help them craft effective policies.

HEPEX: The Hydrological Ensemble Prediction Experiment - Schaake, John C.; Hamill, Thomas M.; Buizza, Roberto; Clark, Martyn (Bulletin of the American Meteorological Society, 2007)
Keywords: Ouvrage_Collectif_Numéro1

At what scales do climate variability and land cover change impact on flooding and low flows? - Blöschl, Günter; Ardoin-Bardin, Sandra; Bonell, Mike; Dorninger, Manfred; Goodrich, David; Gutknecht, Dieter; Matamoros, David; Merz, Bruno; Shand, Paul; Szolgay, Jan (Hydrological Processes, 2007)
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/hyp.6669
Keywords: Ouvrage_Collectif_Numéro1